INTERPRETATION AS A PERVADING PROBLEM IN LEGAL TRANSLATION - FLÖTER-DURR, Margarete (Comparative Legilinguistics, 2019)
In the context of the quantitative shift in the translation field, both pragmatic and legal, this article aims to return to the role of interpretation and meaning concepts and to place them back at the centre of legal translation concerns. Starting from the observation of the necessity of interpretation, it is a question of highlighting the social anchoring of any translation as an act of communication and the inadequacy of the paradigm of equivalence (Sandrini, 2017) which results from it. Based on Schütz’s theory, the concepts of relevance and stock of knowledge and their role in translation will be highlighted (Schütz, 2004b). Finally, the outlines of a practical method of translation based on relevance and usage (Wittgenstein, 2004) will be outlined.